(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The cyclic (2+2) template condensation of pyridine-2,6-dicarboxaldehyde with 1,2-bis(2- aminoethoxy) ethane using Pb(SCN)2 as the metal source gave dinuclear lead (II) complex, Pb2L1(SCN)4 (1), where L1 is tetra-Schiff-base macrocycle. Treatment of 1 with NaBH4 in methanol gave a metal-free reduced macrocycle L2 which has been characterized by 1HNMR and ESI-MS spectroscopy. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7971 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 61-65, 2011